Shoot proliferation and organogenesis on Arbutus unedo: physiological analysis under water stress - J.F. Martins; S. Correia; B. Correia; G. Pinto; J.M. Canhoto (Biologia Plantarum, 2019)
Strawberry tree (Arbutus unedo) is a small perennial tree that grows spontaneously in the Mediterranean basin, Ireland, and Portugal. In this work, strawberry tree clones were established in vitro from epicormic shoots obtained from a young tree, an adult tree, and from a seedling. They were propagated by axillary shoot buds proliferation on solid and in liquid media, and also in a modified De Fossard medium with 9 µM benzylaminopurine. The organogenesis from calli obtained from apical leaves of the in vitro grown shoots from the three genotypes was carried out in the same basal liquid medium supplemented with 9 µM thidiazuron. Micropropagation through organogenesis in liquid medium proved to be more efficient than the other tested methods (considering the number of shoots produced), but the shoots were showing hyperhydricity. Shoots were sucessufully rooted on medium with indole-3-butyric acid and acclimatized ex vitro with rates higher than 90 %. Six month-old plants from the most proliferative genotype (AU1) and propagated in vitro by different methods were submitted to drought stress (no watering for 10 d) and several morphological and physiological parameters were evaluated and compared to a control group (watered to 70 % field capacity). No significant differences were found in plant biomass, root length, and plant height, however, slight differences were observed in water potential, net photosynthetic rate, intercellular CO2 concentration, and stomatal conductance between the plantlets propagated on solid or liquid medium. In general, the responses to drought stress imposed were was similar in plants micropropagated by different propagation methods.